2009
DOI: 10.1016/j.curtheres.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosuvastatin on concentrations of plasma lipids, urine and plasma oxidative stress markers, and plasma high-sensitivity C-reactive protein in hypercholesterolemic patients with and without type 2 diabetes mellitus: A 12-week, open-label, pilot study

Abstract: Rosuvastatin treatment was associated with significant reductions in plasma concentrations of TC, LDL-C, and TG, urine and plasma oxidative stress markers, and plasma hs-CRP in these hypercholesterolemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The 8-OHdG level was elevated in HFD group, however, no significant differences were observed between all the groups tested ( P > 0.05). Studies have shown that elevated levels of MDA [36], AOPP [37], and 8-OHdG [38] in obese animals or humans are associated with several disease conditions including hypertension, diabetes, cardiovascular diseases, and renal diseases [39]. …”
Section: Resultsmentioning
confidence: 99%
“…The 8-OHdG level was elevated in HFD group, however, no significant differences were observed between all the groups tested ( P > 0.05). Studies have shown that elevated levels of MDA [36], AOPP [37], and 8-OHdG [38] in obese animals or humans are associated with several disease conditions including hypertension, diabetes, cardiovascular diseases, and renal diseases [39]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in support of our findings Koksal et al suggested that 10 mg/day ROSUV for 3 months may be helpful in reducing the increased OS observed in T2DM subjects with hyperlipidemia [ 29 ]. Similarly, Yoshino et al suggested that 2.5 mg/day ROSUV for 3 months was associated with a reduction in plasma and urine OS markers in hypercholesterolemic patients [ 30 ]. Nonetheless, the aforementioned studies lack a placebo group, which was included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible patients were randomized (by Online Random Number Generator & Checker) to receive once daily dose of 10 mg atorvastatin or 5 mg rosuvastatin for 8 weeks. 11 The study population comprised 52 hyperlipidemic patients, both male and female 12 , aged 20−75 years [13][14][15] . Eligibility criteria for randomized treatment included fasting LDL-C level >160 mg/dL and fasting triglyceride level <400 mg/dL.…”
Section: Methodsmentioning
confidence: 99%